Integrasi Model Inkuiri dan Literasi Saintifik dalam Pembelajaran Sistem Ekskresi untuk Siswa Sekolah Menengah Atas - Anna Kosasih; Rahmawati Firdaus (Insight of Biology, 2025)
This study aims to analyze the effectiveness of integrating the inquiry-based learning model with a scientific literacy approach to enhance students’ conceptual understanding and scientific competencies in the excretory system topic, in alignment with the principles of the Merdeka Curriculum. The research was conducted at SMA Negeri 2 Praya, Central Lombok Regency, West Nusa Tenggara, using a quasi-experimental design with a pretest-posttest control group format. The sample consisted of two Grade XI science classes selected through purposive sampling: one as the experimental group, which received inquiry-based instruction integrated with scientific literacy, and the other as the control group, which received conventional instruction. Data collection instruments included multiple-choice tests to assess conceptual understanding and observation sheets to evaluate students’ scientific skills and active engagement during learning activities. Data analysis using the t-test revealed a statistically significant difference between the experimental and control groups in terms of both conceptual understanding (p < 0.05) and scientific competency. The findings indicate that the implementation of an inquiry model aligned with the learning outcomes of the Merdeka Curriculum effectively fosters contextual, student-centered, and exploratory learning. This instructional strategy is recommended as an alternative approach in biology education that supports the development of the Profil Pelajar Pancasila and prepares students for future global challenges.